Escalation and De-Escalation of Commitment to Information Systems Projects: Insights from an Approach-Avoidance Process Model - PAN, Gary (Institutional Knowledge at Singapore Management University, 2006)
We view escalation and de-escalation of commitment as processes involving recurring instances of approach-avoidance conflict. This paper outlines an approach-avoidance process model for describing and analyzing escalation and de-escalation of commitment in information systems projects. In the model, the sequential mapping of project events is integrated with a model of approach-avoidance conflict that identifies periods of gradual evolution at two separate levels of social analysis (project and work) that are punctuated by sudden, revolutionary periods of rapid change. By conceiving the processes of commitment escalation and de-escalation as sequences of events involving approach-avoidance conflicts, researchers may develop a deeper understanding of how and why projects escalate and de-escalate. Practitioners can also utilize the model in postmortem analyses of projects which have faced escalation to diagnose the issues surrounding the escalation and devise useful de-escalation strategies for future project development. The model is developed and illustrated with a case study that exhibits both project escalation and de-escalation conditions.